CAN COGNITIVE BEHAVIOR THERAPY WITH COGNITIVE RESTRUCTURING TECHNIQUES REDUCE INFERIORITY IN STUDENTS? - Dina Ayu Saputri; Edris Zamroni; Indah Lestari (Jurnal Konseling Pendidikan Islam, 2026)
Individuals with feelings of inferiority tend to mask their shortcomings due to a lack of self-realization, which impacts various aspects of life such as career, social relationships, and mental health. Based on the results of observations and interviews with BK teachers of SMP Negeri 3 Jekulo Kudus, it was found that students showed symptoms of inferiority such as withdrawal, indifference, envy, and feeling uncomfortable when working in a group. This study uses a case study method in AB students of grade VIII E with an individual counseling approach using Cognitive Behavior Therapy (CBT), specifically the Cognitive Restructuring technique  to correct cognitive distortions that affect the counselor's negative beliefs. Data was collected through interviews with BK teachers and counselors, as well as direct observations at school. Data analysis was carried out using the Miles & Huberman model. The results of the study show that the factors that cause the inferiority of AB students come from internal factors such as negative mindsets, feelings of inferiority, and difficulty interacting, as well as external factors in the form of lack of family support and social pressure. CBT interventions have been shown to be effective in helping ABs identify and change negative mindsets to be more adaptive. After the counseling process, AB showed significant improvements in self-confidence, social interaction skills, and emotional management.